Exploring the role of intellectual capital in supply chain intelligence integration. Issue 5 (11th June 2018) - Shou, Yongyi; Hu, Wenjin; Xu, Yongmei
Abstract : Purpose: The purpose of this paper is to explore the role of intellectual capital (IC) in supply chain intelligence integration (SCII) and the interrelationships of the three components of IC (i.e. human capital (HC), structural capital (SC) and relational capital (RC)) in the supply chain context. Design/methodology/approach: This paper conducted an empirical study by using primary data from 389 sample firms. The authors applied structural equation modeling to test the proposed hypotheses. Findings: The results indicate that both HC and RC have direct impact on SCII, whereas SC only influences SCII through RC. Originality/value: This study evidences that IC is an enabler of SCII. Furthermore, this study reveals the interrelationships of human, structural and RC.